Knee alignment in professional tennis players - Maquirriain, J. (2001)
Little is known regarding joint alignment in athletes and its relationships with performance and injuries. The purpose of this study was to measure lower limb alignment and knee geometry in professional tennis players and to compare these data with those from non-athletic subjects.